2022
DOI: 10.1007/s43615-022-00160-2
|View full text |Cite
|
Sign up to set email alerts
|

Nexus Between Life Cycle Assessment, Circularity and Sustainability Indicators—Part II: Experimentations

Abstract: Considering the growing number of metrics and indicators to assess the circular economy transition, it is paramount to shed light on how they complement and differ from traditional approaches, such as life cycle assessment or sustainability performance indicators. This study provides new empirical insights on the correlation between life cycle assessment, circularity, and sustainability indicator-based approaches to design circular and sustainable products. Specifically, the importance lies in analyzing how th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
(24 reference statements)
0
5
0
1
Order By: Relevance
“…In practice, repairability has to compete with the value addition post-repair as well as the reduced cost of repair than replacement of products (i.e., the potential cannibalization effect from a growing market share of repaired products has to be further studied). Last but not least, following the experimental work of Terzioğlu and Wever (2021) on 52 repair projects with master students, we encourage fostering circular design or design for Re-X (reuse, repair, recycling) into design education to make students aware of the residual value/potential of their broken devices, as well as to teach them the competencies (including both theoretical knowledge and technical skills) and to give them the appropriate tools to perform repair activities and to able to quantify the potential environmental and economic savings associated to an increased circularity (Saidani et al, 2022).…”
Section: Perspectives For Future Workmentioning
confidence: 99%
“…In practice, repairability has to compete with the value addition post-repair as well as the reduced cost of repair than replacement of products (i.e., the potential cannibalization effect from a growing market share of repaired products has to be further studied). Last but not least, following the experimental work of Terzioğlu and Wever (2021) on 52 repair projects with master students, we encourage fostering circular design or design for Re-X (reuse, repair, recycling) into design education to make students aware of the residual value/potential of their broken devices, as well as to teach them the competencies (including both theoretical knowledge and technical skills) and to give them the appropriate tools to perform repair activities and to able to quantify the potential environmental and economic savings associated to an increased circularity (Saidani et al, 2022).…”
Section: Perspectives For Future Workmentioning
confidence: 99%
“…On this basis, realistic scenarios could be generated to compare the environmental impact of different end-of-life and circularity pathways. Importantly, the LCA and CI results can be complemented with leading sustainability indicators (Kravchenko et al, 2020;Saidani et al, 2022) to ensure that an increased circularity leads to positive benefits on the three pillars of sustainable development. Last but not least, as the industrial participants found both frameworks easy to use and efficient, all the details and resources used to conduct, replicate, or adapt such workshops in various industrial contexts can be made available on demand.…”
Section: Improvementsmentioning
confidence: 99%
“…Система мониторинга развития экономики замкнутого цикла, который регулярно проводится и разрабатывается Еврокомиссией и Евростатом с 2015 г., включает в себя десять индикаторов, которые, с одной стороны, просты, информативны и доступны, а с другой -достаточно полно отображают уровень развития циркулярной экономики. Следующим шагом исследователей в изучении и развитии методов оценки циркулярной экономики является поиск взаимосвязи между оценкой жизненного цикла, циркулярности и показателей устойчивости Saidani, Cluzel, Leroy et al, 2022].…”
Section: методы и источники информации для оценки циркуляризации экон...unclassified